2023
DOI: 10.1007/s10792-023-02896-8
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of a posterior chamber phakic intraocular lens with a central hole for correction of myopia

Christoph Lwowski,
Karel Van Keer,
Tim Ruscher
et al.

Abstract: Purpose To evaluate intermediate and long-term visual outcomes and safety of a phakic intraocular posterior chamber lens with a central hole (ICL V4c) for myopic eyes. Methods Retrospective, consecutive case study of patients that uneventfully received a ICL V4c for myopia correction, with a 5-year postoperative follow-up. Department of Ophthalmology, Goethe University Frankfurt, Germany. Results From 241 eyes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Multiple meta-analyses have demonstrated that ICL implantation can achieve comparable or superior effectiveness and safety in correcting moderate-to-high myopia compared with laser in situ keratomileusis (LASIK) and small incision lenticule extraction (SMILE) (5,(12)(13)(14)(15). Notably, several clinical follow-up studies conducted over 5 years have consistently demonstrated the favorable stability of ICL and TICL (16)(17)(18)(19). However, in super-high myopia cases with a diopter (D) < −12D, stability after ICL implantation may be slightly compromised, leading to continued myopia increase and axial growth (20,21).…”
Section: Research Frontiersmentioning
confidence: 99%
“…Multiple meta-analyses have demonstrated that ICL implantation can achieve comparable or superior effectiveness and safety in correcting moderate-to-high myopia compared with laser in situ keratomileusis (LASIK) and small incision lenticule extraction (SMILE) (5,(12)(13)(14)(15). Notably, several clinical follow-up studies conducted over 5 years have consistently demonstrated the favorable stability of ICL and TICL (16)(17)(18)(19). However, in super-high myopia cases with a diopter (D) < −12D, stability after ICL implantation may be slightly compromised, leading to continued myopia increase and axial growth (20,21).…”
Section: Research Frontiersmentioning
confidence: 99%